PENGEMBANGAN PRODUK IKAN HIAS MELALUI PELATIHAN PEMBUATAN AKUARIUM - Abdullah, Akmal; Kasmi, Mauli; Karma, Karma; Ilyas, Ilyas (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2020)
The ornamental fish business over time experiences an increasing trend. The large supply of ornamental fish that enter Makassar city shows that the public's interest in ornamental fish in Makassar city is quite high, thus making the ornamental fish business as a very promising opportunity to be pursued. The objective of the Regional Superior Product Development Program (PPPUD) is to develop the business activities of SME partners to be more economically independent and improve softskill and hardskiil skills about ornamental fish business and aquarium manufacturing. The method used is to conduct training and introduction activities on the business of ornamental fish on a commercial scale followed by demonstration of the procedures for the creation of aquariums to SMEs and fishing groups who become partners. The result obtained from this activity is that SMEs and Catcher Groups understand about ornamental fish business activities in this case the manufacture of aquariums as diversified ornamental fishing efforts that have been pursued by both SME partners. Partners are expected to fill the local market that has not been filled and compete in the aquarium and ornamental fish business. With this activity, there is an increase in commercial-scale aquarium manufacturing skills for the local market, so that both SMEs can sell ornamental fish production and can also sell aquariums and their contents so that the revenue from SMEs is increased.